If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3t + 1)(-1 + t) = 1 Reorder the terms: (1 + 3t)(-1 + t) = 1 Multiply (1 + 3t) * (-1 + t) (1(-1 + t) + 3t * (-1 + t)) = 1 ((-1 * 1 + t * 1) + 3t * (-1 + t)) = 1 ((-1 + 1t) + 3t * (-1 + t)) = 1 (-1 + 1t + (-1 * 3t + t * 3t)) = 1 (-1 + 1t + (-3t + 3t2)) = 1 Combine like terms: 1t + -3t = -2t (-1 + -2t + 3t2) = 1 Solving -1 + -2t + 3t2 = 1 Solving for variable 't'. Reorder the terms: -1 + -1 + -2t + 3t2 = 1 + -1 Combine like terms: -1 + -1 = -2 -2 + -2t + 3t2 = 1 + -1 Combine like terms: 1 + -1 = 0 -2 + -2t + 3t2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. -0.6666666667 + -0.6666666667t + t2 = 0 Move the constant term to the right: Add '0.6666666667' to each side of the equation. -0.6666666667 + -0.6666666667t + 0.6666666667 + t2 = 0 + 0.6666666667 Reorder the terms: -0.6666666667 + 0.6666666667 + -0.6666666667t + t2 = 0 + 0.6666666667 Combine like terms: -0.6666666667 + 0.6666666667 = 0.0000000000 0.0000000000 + -0.6666666667t + t2 = 0 + 0.6666666667 -0.6666666667t + t2 = 0 + 0.6666666667 Combine like terms: 0 + 0.6666666667 = 0.6666666667 -0.6666666667t + t2 = 0.6666666667 The t term is -0.6666666667t. Take half its coefficient (-0.3333333334). Square it (0.1111111112) and add it to both sides. Add '0.1111111112' to each side of the equation. -0.6666666667t + 0.1111111112 + t2 = 0.6666666667 + 0.1111111112 Reorder the terms: 0.1111111112 + -0.6666666667t + t2 = 0.6666666667 + 0.1111111112 Combine like terms: 0.6666666667 + 0.1111111112 = 0.7777777779 0.1111111112 + -0.6666666667t + t2 = 0.7777777779 Factor a perfect square on the left side: (t + -0.3333333334)(t + -0.3333333334) = 0.7777777779 Calculate the square root of the right side: 0.881917104 Break this problem into two subproblems by setting (t + -0.3333333334) equal to 0.881917104 and -0.881917104.Subproblem 1
t + -0.3333333334 = 0.881917104 Simplifying t + -0.3333333334 = 0.881917104 Reorder the terms: -0.3333333334 + t = 0.881917104 Solving -0.3333333334 + t = 0.881917104 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '0.3333333334' to each side of the equation. -0.3333333334 + 0.3333333334 + t = 0.881917104 + 0.3333333334 Combine like terms: -0.3333333334 + 0.3333333334 = 0.0000000000 0.0000000000 + t = 0.881917104 + 0.3333333334 t = 0.881917104 + 0.3333333334 Combine like terms: 0.881917104 + 0.3333333334 = 1.2152504374 t = 1.2152504374 Simplifying t = 1.2152504374Subproblem 2
t + -0.3333333334 = -0.881917104 Simplifying t + -0.3333333334 = -0.881917104 Reorder the terms: -0.3333333334 + t = -0.881917104 Solving -0.3333333334 + t = -0.881917104 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '0.3333333334' to each side of the equation. -0.3333333334 + 0.3333333334 + t = -0.881917104 + 0.3333333334 Combine like terms: -0.3333333334 + 0.3333333334 = 0.0000000000 0.0000000000 + t = -0.881917104 + 0.3333333334 t = -0.881917104 + 0.3333333334 Combine like terms: -0.881917104 + 0.3333333334 = -0.5485837706 t = -0.5485837706 Simplifying t = -0.5485837706Solution
The solution to the problem is based on the solutions from the subproblems. t = {1.2152504374, -0.5485837706}
| x^2-16x+60=0 | | 0.9x+2.3x=-6.4 | | 0.7c-10=0.5 | | 15m+4-m=-32 | | y=2*0+1 | | x^2+8x+0=0 | | y=2*-1+1 | | 3(5x+2)+4(3x+5)=0 | | y=2*-2+1 | | 8y-7=-12y+2 | | x-4=-x+2 | | 16+2=9 | | 3x+4=2x+9 | | 2x-4y=16 | | 4x^3-8x=14x^2 | | t=42 | | 7(a+x)=b-a+2x | | 525.00+5.00x=1500 | | -3a+2b= | | -5x*-2x= | | 5x*(-2x)= | | -2*-1+y=1 | | 5*2x= | | -2*-2+y=1 | | 5+2x= | | y+5*1=0 | | -x*x= | | y+5*0=0 | | 5(3-4x)=255 | | y+5*-1=0 | | -3x*(-x)= | | y+5*-2=0 |